Effect of chorionic villus sampling and early pregnancy counselling on uptake of prenatal diagnosis. Issue 6545 (23rd August 1986) - Knott, P D; Ward, R H; Lucas, M K
Abstract : An early pregnancy counselling clinic was introduced to improve the uptake of prenatal diagnosis and to offer chorionic villus sampling to women aged 38 and over by their expected date of delivery. Ninety eight (62%) unselected older mothers were seen before 11 weeks' gestation, and 23 (32%) of those with viable pregnancies elected to undergo chorionic villus sampling compared with 38 (52%) electing amniocentesis. A quarter of the patients booking before 11 weeks had a miscarriage. Because of the future potential demand for chorionic villus sampling counselling during pregnancy and referral of eligible patients should occur as early as possible.